Immune Response and Prognosis of Chronic Kidney Disease Patients Undergoing Hemodialysis Against COVID-19: A Systematic Review - Nurul Hanifa; Riri Andri Muzasti (Jurnal Kedokteran Diponegoro, 2022)
Background: Chronic kidney disease (CKD) patients are characterized by immune response dysfunction which increased susceptibility to infections. CKD is one of the Coronavirus disease-2019 (COVID-19) comorbidity that generally has a poor clinical outcome and patients undergoing hemodialysis had a 50% hospitalization rate and 20%-30% mortality rate. Seroconversion after confirmation of COVID-19 infection is close to 100% in the dialysis population, but the durability of the immune response and the extent as a protection against infection remains unclear. This study aimed to determine the immune response and prognosis of CKD patients undergoing hemodialysis against COVID-19.